The Gauss-Manin connection for the Legendre family of elliptic curves (2021)
We study the Picard-Fuchs equation from both the classical and modern perspectives. The classical perspective uses only elementary calculus on manifolds, while the modern perspective looks at the problem using the tools of sheaf theory and cohomology.